2014
DOI: 10.1111/rssb.12099
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of Heteroscedastic Extremes

Abstract: Summary We extend classical extreme value theory to non‐identically distributed observations. When the tails of the distribution are proportional much of extreme value statistics remains valid. The proportionality function for the tails can be estimated non‐parametrically along with the (common) extreme value index. For a positive extreme value index, joint asymptotic normality of both estimators is shown; they are asymptotically independent. We also establish asymptotic normality of a forecasted high quantile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(141 citation statements)
references
References 18 publications
7
131
3
Order By: Relevance
“…The estimation of γ (x 0 ) has been addressed by many authors such as Smith (1990), Smith (1989), and Chavez-Demoulin and Davison (2005). Einmahl et al (2014) consider the case where survival functions S x 1 (·), . .…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of γ (x 0 ) has been addressed by many authors such as Smith (1990), Smith (1989), and Chavez-Demoulin and Davison (2005). Einmahl et al (2014) consider the case where survival functions S x 1 (·), . .…”
Section: Introductionmentioning
confidence: 99%
“…Of course time series of daily temperatures are neither independent (they are somewhat autocorrelated) nor identically distributed (their distributions vary within a year). There is however theoretical justification for the use of GEV distributions in our case: it has been shown that the independence assumption can be relaxed for weakly dependent stationary time series (Leadbetter et al, 1983;Hsing, 1991), and Einmahl et al (2016) extended the theory to non-identically distributed observations with conditions on the tail distributions (e.g., distributions share a common absolute maximum). In this work, we explicitly assess whether inferred GEV distributions actually provide an adequate description of the data set in question.…”
Section: Statistical Backgroundmentioning
confidence: 99%
“…However, in the previous references it assumed that the observations are identically distributed. Recently, Einmahl et al [2016] showed consistency of classical tail estimators under slightly weaker assumptions called heteroscedastic extremes, but still they need that the tail behavior, i.e., the extreme value index γ is the same for all observations. In analogy to the previous subsection, we first check whether the extreme value index of monthly maximal flows is constant over the whole observation period.…”
Section: Monthly Maximal Flows At the Mulde River Basin In Germanymentioning
confidence: 99%
“…For many environmental applications the main interest is in the frequency of hazardous events, e.g., extreme precipitations and floods. Accordingly, there is a number of articles introducing methodology for change-points [Jarušková and Rencová, 2008;Kim and Lee, 2009;Dierckx and Teugels, 2010;Dupuis et al, 2015;Bücher et al, 2015;Kojadinovic and Naveau, 2015] and regression/trend analysis [Chavez-Demoulin and Davison, 2005;Wang and Tsai, 2009;Gardes and Girard, 2010;Dierckx, 2011;Wang et al, 2012;Wang and Li, 2013;Einmahl et al, 2016;de Haan et al, 2015] of extremes, just to name a few recent contributions. For a case study and an overview of many flood trend analyses we refer to Mediero et al [2014].…”
Section: Introductionmentioning
confidence: 99%